Innovative solutions for global water quality challenges: insights from a collaborative hackathon event - Chernov, Igor; Elsler, Melchior; Maillart, Thomas; Cacciatori, Caterina; Tavazzi, Simona; Gawlik, Bernd Manfred; Vystavna, Yuliya; Anastasaki, Afroditi; DuBois, Carolyn; Warner, Stuart; Neely, Merrie Beth; Muziasari, Windi; et al. (Frontiers in Water, 2024)
Addressing the global water quality challenges requires collaborative efforts, multidisciplinary approaches, and innovative solutions. Here we report on the success of a special collective intelligence “hackathon event,” organized by five United Nations agencies and the European Commission, with the aim of reinventing engagement with diverse experts and stakeholders to tackle real-world challenges in water quality monitoring and assessment. Participants from diverse backgrounds and regions convened to devise inventive solutions in four key challenge areas, including (1) transformation of water quality data into water stewardship action, (2) empowering citizen scientists to improve water quality, (3) incorporation of Indigenous communities and their water quality knowledge in global information systems, and (4) routine monitoring of antimicrobial resistance in water. The hackathon approach fosters collective intelligence in a safe, creative and collaborative environment, enabling participants to harness their collective knowledge, expertise and skills. Key outcomes were conceptualizing practical frameworks and tailored toolboxes for diverse water quality innovations to improve monitoring, empower communities, and support policy-making. Emphasis was placed on the purpose and value of interdisciplinary collaborations to address complex global challenges, showcasing synergies between technology, environmental science, and social engagement. Hackathons are catalysts for collaborative innovation which unlock future endeavors in harnessing collective intelligence to safeguard our most precious resource – water.